2004
DOI: 10.1177/1365480204048930
|View full text |Cite
|
Sign up to set email alerts
|

Understanding creativity and its implications for schools

Abstract: After issuing a flood of missives about education during its time in office, the Government is now actively encouraging the exploitation of creativity and offering schools the opportunity to be more flexible in their interpretation and teaching of the curriculum. This apparent change of heart has left school leaders and classroom practitioners with the formidable task of interpreting and evaluating its implications, in which they face two main challenges. First, to understand what creativity means and how it c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 13 publications
0
8
0
4
Order By: Relevance
“…In practice, though, teachers' creativity is under the pressure of national testing (Aktas, 2016;Aljughaiman & Mowrer-Reynolds, 2005;Amabile, 1996;Craft, 2001;Gordon, 1999;Hayes, 2004) and supporting creativity may be perceived as a paradox or luxury in such a performance driven system (Grainger, Barnes, & Scoff ham, 2004;Hartley, 2003;Prentice, 2000). Dobbins (2009) found that teachers' creativity is restricted by curriculum and learning objectives.…”
Section: Teachers' Creativitymentioning
confidence: 99%
“…In practice, though, teachers' creativity is under the pressure of national testing (Aktas, 2016;Aljughaiman & Mowrer-Reynolds, 2005;Amabile, 1996;Craft, 2001;Gordon, 1999;Hayes, 2004) and supporting creativity may be perceived as a paradox or luxury in such a performance driven system (Grainger, Barnes, & Scoff ham, 2004;Hartley, 2003;Prentice, 2000). Dobbins (2009) found that teachers' creativity is restricted by curriculum and learning objectives.…”
Section: Teachers' Creativitymentioning
confidence: 99%
“…In other countries, such as United States and Australia, creativity is not explicitly highlighted in the mathematics curricula but elements related to creativity, such as fluency, flexibility, and novelty in problem solving or conceptual understanding, are pursued (Coil 2013). Researchers in different parts of the world have indicated that due to an examination-driven environment, teachers feel burdened when asked to apply creativity education to their own classes or apply it only superficially even though they sympathize with the idea (Craft 2005;Hayes 2004;Maisuria 2005;Zawojewski and McCarthy 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Another document which called for creativity in primary education was the National Primary Strategy for primary schools, Excellence and Enjoyment, (Hayes, 2004). The Office for Standards in Education (Ofsted) published this report in 2003 and in this they identified creativity as "a significant factor in educational experience" (Jeffrey, 2005).…”
Section: The Inclusion Of Creativity Within Educationmentioning
confidence: 99%